The effect of nighttime trading of futures markets on information flows: evidence from China - Hung-Gay Fung; Liuqing Mai; Lin Zhao (China Finance and Economic Review, 2016)
Background: In the past couple of years, China's futures exchanges have launched nighttime trading sessions. Methods: We use daily data from 23 commodity futures to investigate the impact of this important policy change. Results: Our findings suggest that the launching of nighttime trading effectively improved the efficiency of futures prices and reduced the volatility of prices. The normality of returns improves during the post-nighttime trading period. As documented in the literature, the interactions between trading activities (i.e., trading volume and open interest) and volatility conform better to the observed patterns in developed markets. Conclusions: This study provides sound evidence that China has taken steady steps toward its goal of establishing price-setting power in key commodities on world financial markets.
Keywords: G13; G14; G15; 330; China's futures market; Futures price and volatility; Nighttime trading